Explicit and implicit weight bias among health care students: a cross-sectional study of 39 Australian universities. (April 2023) - Jayawickrama, Ravisha S.; O'Connor, Moira; Flint, Stuart W.; Hemmingsson, Erik; Lawrence, Blake J.
Summary: Background: Weight bias exhibited by health care students may continue into their future practice, compromising the provision of care that people living with overweight or obesity receive. This highlights the need to comprehensively examine the extent to which weight bias is present among health care students and the factors that may be associated with students' weight bias. Methods: In this cross-sectional study, Australian university students enrolled in health care courses were invited via social media advertisements, snowball and convenience sampling, and by making direct contact with universities to complete an online survey. Students provided demographic information including discipline of study, perceived weight status, and state of residence. Students then completed several measures which assessed their explicit and implicit weight bias, and empathy. Descriptive statistics established the presence of explicit and implicit weight bias, and ANCOVAs, ANOVA, and multiple regression analyses were conducted to examine the potential factors associated with students' exhibited weight bias. Findings: Between March 08, 2022, and March 15, 2022, 900 eligible health care students attending 39 Australian universities participated in the study. Students reported varying levels of explicit and implicit weight bias, with minimal differences between disciplines on most outcome measures. Students who identified as men (vs. women) exhibited higher of both explicit and implicit bias (Beliefs About Obese Persons (BAOP): p  = 0.0002, Antifat Attitudes Questionnaire (AFA)—Dislike: p  = 0.019, AFA Willpower p  < 0.0001, Empathy for Obese Patients: p  = 0.0011, Implicit Association Test: p  = 0.022), and students who displayed greater (vs. less) empathic concern exhibited lower levels of explicit bias (BAOP, AFA Dislike and Willpower, and Empathy for Obese Patients: p  < 0.0001). Having witnessed the enactment of weight stigma sporadically (vs. regularly) by role models was associated with greater attribution of the causes of obesity to willpower (a few times a month vs. daily: p  = 0.020, a few times a year vs. daily: p  = 0.022), and less time spent with people living with overweight or obesity outside of study was associated with more dislike (a few times a month vs. daily: p  = 0.0048, once a month vs. daily: p  = 0.0002) and less fear of fat (once a month vs. daily: p  = 0.036, and once a month vs. a few times a week: p  = 0.0028). Interpretation: Results demonstrate the presence of both explicit and implicit weight bias among Australian health care students. Several characteristics and experiences of students were associated with their weight bias. Validity of the exhibited weight bias should be established in practical interactions with people living with overweight or obesity and novel interventions should be developed to ameliorate weight bias. Funding: Research Training Program (RTP) Scholarship, Australian Government, Department of Education.